Galatians 5.11: Evidence of an Early Law-observant Mission by Paul? - Campbell, Douglas A. (New Testament studies, 2011)
Galatians 5.11 refers to Paul ‘proclaiming circumcision’—a proposition that he is concerned to refute because he constructs two compact but powerful inferences designed to falsify it. One argues from present persecution, the other from the cross. Following a precise reconstruction of these it can be shown that the three main previous interpretations of the reference of Paul's ‘proclamation of circumcision’ are dubious, whether in terms of a blatantly false charge by opponents, a phase in Paul's pre-Christian Jewish life, or an occasional apostolic mission to Jews. A fourth, embarrassing reading is more likely, especially when other comparable missionary work is considered. Early on Paul proclaimed a fully law-observant gospel to pagans that included circumcision, but then later revised his praxis.